I did not die - Mzamo, Tebello (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2017)
My novella is about a mine worker and his family. Set in both Lesotho and South Africa, it engages the effects of migrant labour on families in post-apartheid South Africa. Told through the eyes of the different family members, the narrative uses shifting points of view and moves fluidly through time to present an intimate but complex view of the lives of ordinary working class people. It incorporates witchcraft and ghosts to reveal the blurred lines between the realms of life and death. This collection is inspired by my own father who is a former mine worker. I am influenced by Joyce Carol Oates and Chibundu Onuzo's darkly realistic style, Veronique Tadjo's explorations of migration and death, the family chronicles of Chimamanda Ngozi Adichie and Yvonne Adhiambo Owuor. I am also inspired by female fantasy and horror writers such as those collected in Ann and Jeff VanderMeer's anthology, Sisters of the Revolution: A Feminist Speculative Fiction Anthology.
Keywords: Uncatalogued